SECURITIES MARKET REGULATION: NATIONAL AND INTERNATIONAL ASPECTS OF THE KEY INSTRUMENTS’ FUNCTIONING - Zubenko, Vyacheslav; Danilkevich, Lyudmila; Lozitskaya, Olga; Stepanov, Dmitry (Revista Inclusiones, 2020)
The article is devoted to the analysis of the current legal regulation of the securities market in the Russian Federation. The securities market in Russia is relatively young and, as a result, many aspects of it are not clearly regulated by Russian law, which naturally creates numerous problems for participants. The purpose of this study is to analyze the legal regulation of the securities market, summarize the results, present conclusions, and offer recommendations for improving the regulatory framework to address the identified problems. The article shows the great importance of the securities market in the modern economic sphere, the dynamics and volume of investments in major financial instruments, and prospects for further development.